Assessment of the Brazilian postgraduate evaluation system - McManus, Concepta; Baeta Neves, Abilio Afonso; Souza Filho, Antonio Gomes; Rosa, Arthur Antonio Silva; Carvalho, Carlos Henrique; Freire, Denise Maria Guimarães; Fioravanti, Maria Clorinda Soares; Báo, Sonia Nair; de Medeiros, Isac Almeida; Diniz-Filho, José Alexandre; Diaz, Bruno Lourenço; de Carvalho, Ernani Rodrigues; et al. (Frontiers in Education, 2022)
The present study provided an overview of evaluation data from the "Sucupira Platform", questionnaires with post-graduate deans, discussion forums, and international databases to assess the Brazilian post-graduate evaluation system. The system is highly standardised and homogenous throughout the country with little flexibility. There is a disconnect with ongoing changes in international graduate studies, especially regarding the possibility of adopting flexible and temporary doctoral projects in international partnerships. The evaluation focuses mainly on process, not results, impact, and social relevance. Although the current system requires strategic planning and self-assessment, these are not used when evaluating results. The system should be sensitive to differences, valuing the diversity of institutional projects. Changes in the evaluation require a clear timeline and careful definition of indicators. The improvement of information collection must occur in coordination with CNPq, and the new platform must be able to import information from various sources (RAIS, Lattes, WIPO, PrInt, etc.). According to their purposes, the separate indication in CAPES' spreadsheets on the legal status of private and community/confessional institutions is fundamental for improved data analysis. The assignment of grades rather than scores (e.g. in implementation, consolidated nationally/internationally) is questioned.